GOGOL: ACADEMIC AND COMPLETE - Yuri V. Mann (Studia Litterarum)
The ever-increasing international interest to Gogol explains the necessity of publishing a new edition of his works. The present Complete Collection of Gogol’s Works and Letters is an academic edition prepared and published by the A. M. Gorky Institute of World Literature of the Russian Academy of Sciences. It draws on rich experience of studying and publishing Gogol’s heritage in Russia but at the same time questions and underscores Gogol’s relevance for the modern reader and his place in the world culture of our time. It intends to fill in the gaps left by the previous scholarly tradition that failed to recognize some of Gogol’s texts as part of his heritage. Such are, for example, dedicatory descriptions in books and business notes. The present edition accounts not only for the completeness of texts but also for their place within the body of Gogol’s work, as part of his life-long creative process. By counterpoising different editions, it attempts to trace down the dynamics of Gogol’s creative thought while at the same time underscores the autonomy and relevance of each period in his career. For example, this collection publishes two different versions (editions) of the same work: while the most recent version has become canonical at the expense of the preceding one, the latter still preserves its meaning and historical relevance. The present edition has the advantage over its predecessors since it has an actual, physical opportunity to erase the gaps, e.g. to publish the hitherto unpublished texts. However, the editors realize that new, hitherto unknown gaps may appear and the present edition will become, in its turn, outdated. At this point, there will be a necessity in the new edition.